The Potential Bryophyta Diversity On Riverside Susup As Science Teaching Materials For SMP - Ronggo Waskito, Jefri; Karyadi, Bhakti; Sutarno; Parlindungan, Deni; Ekaputri, Rendi Zulni; Sakti, Indra; Uliyandari, Mellyta (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the diversity of bryophyta on the riverside Susup as learning material in the form of Learning Unit Books (BUP). The research method used is Research and Development which is limited to needs analysis and BUP design. Moss plant diversity samples were obtained using a purposive sampling technique. Found 10 families, 13 types of species and 80 total bryophyta colonies on the banks of the river. The diversity index (H') ranges from 1.474 - 1.911 which includes the medium category, the evenness index (E) ranges from 0.822 - 0.940 which includes the high category and the dominance index (C) ranges from 0.1550 - 0.3056 which includes the low category. These findings are then used as teaching materials for designing BUP for SMP.